Nisekoi : False love. Vol. 8, Last minute - Komi, Naoshi, 1986- (Shonen Jump manga., 2015)
"As Chitoge gets more and more acclimated to her new life in Japan, she finds herself spending more time with Raku and her newfound friends, most of whom have a crush on Raku as well! But now that it's Valentine's Day, will Chitoge and friends find the nerve to give Raku their homemade chocolates?" --